Roles of the m6A methyltransferases METTL3, METTL14, and WTAP in pulmonary tuberculosis - Zhang, Tian-Ping; Li, Rui; Wang, Li-Jun; Huang, Qian; Li, Hong-Miao (Frontiers in Immunology, 2022)
Objective: The aim of the current study was to investigate the contributing role of gene variation and transcription levels among the m6A methyltransferases METTL3, METTL14, and WTAP in pulmonary tuberculosis (PTB). Methods: A case-control study including 461 PTB patients and 467 normal controls was designed for genotyping. Three SNPs in METTL3 (rs1061027, rs1139130, rs1061026), three SNPs in METTL14 (rs62328061, rs4834698, rs1064034), and two SNPs in WTAP (rs1853259, rs11752345) were genotyped via the improved multiple ligase detection reaction. METTL3, METTL14, and WTAP transcription levels were determined in 78 PTB patients and 86 controls via quantitative realtime reverse-transcription PCR. Results: Frequencies of the METTL14 rs62328061 GG genotype, WTAP rs11752345 CT genotype, and T allele were significantly increased in PTB patients compared to controls. An increased risk of rs62328061 was detected in a recessive model, and a decreased risk of rs11752345 was detected in a dominant model in the PTB group. METTL3 gene variation was not associated with PTB risk. The METTL3 rs1139130 GG genotype was significantly increased with drug resistance, and the G allele was significantly decreased with drug-induced liver injury in PTB patients. A reduced frequency of the METTL14 rs62328061 G allele was associated with leukopenia, a reduced frequency of the WTAP rs11752345 T allele was associated with sputum smear positivity, and a higher frequency of the METTL14 rs4834698 TC genotype was evident in PTB patients with hypoproteinemia. Compared to controls, METTL3, METTL14, and WTAP transcription levels in PTB patients were significantly decreased, and the level of WTAP was increased in PTB patients with drug resistance. METTL3 level was negatively associated with erythrocyte sedimentation rate and aspartate aminotransferase, and METTL14 level was negatively correlated with alanine aminotransferase and aspartate aminotransferase. Conclusion: METTL14 rs62328061 and WTAP rs11752345 variants were associated with the genetic background of PTB, and METTL3, METTL14, and WTAP levels were abnormally decreased, suggesting that these m6A methyltransferases may play important roles in PTB.